Energy-Efficient Fire Monitoring over Cluster-Based Wireless Sensor Networks. (28th March 2012) - Ha, Young-guk; Kim, Heemin; Byun, Yung-cheol
Abstract : Uncontrolled fires occurring in wild areas cause significant damage to natural and human resources. Many countries are looking for ways to fight forest fires at an early stage using sensor networks, by integrating IT technologies. Studies in the fire-related sensor network field are broadly classified into efficient processing of fire data on sensor nodes and energy efficiency during communications among wireless sensor nodes in case of fire. Most studies of sensor network energy efficiency so far mainly focus on extending the connectivity of the entire network and minimizing isolated nodes by applying power evenly to each sensor node through efficient cluster-based routing. This paper proposes an energy-efficient fire monitoring protocol over cluster-based sensor networks. The proposed protocol dynamically creates and reorganizes the sensor network cluster hierarchy according to the direction of fire propagation over the sensor network clusters. This paper also presents experimental results to show that the proposed protocol is more energy efficient than fire monitoring with existing cluster-based sensor network protocols.